Pro ASP.NET 4 in VB 2010 - MacDonald, Matthew; Mabbutt, Dan; Freeman, Adam (Apress : Imprint: Apress, 2010)
ASP.NET 4 is the principal standard for creating dynamic web pages on the Windows platform. Pro ASP.NET 4 in VB 2010 raises the bar for high-quality, practical advice on learning and deploying Microsoft's dynamic web solution. This edition is updated with everything you need to come to grips with version 4 of ASP.NET, including coverage of ASP.NET MVC, ASP.NET AJAX 4, ASP.NET Dynamic Data, and Silverlight 3. Seasoned .NET professionals Matthew MacDonald and Mario Szpuszta explain how you can get the most from these groundbreaking new technologies. They cover ASP.NET 4 as a whole, illustrating both the brand-new features and the functionality carried over from previous versions of ASP. This book will give you the knowledge you need to code real ASP.NET 4 applications in the best possible style.